Mylan Fraud: Accounting and Disclosure Considerations - BARANEK, DEVON (The Journal of Accounting and Management, 2022)
This teaching case outlines how Mylan, N.V., a global pharmaceutical company, recently paid nearly 500 million to settle investigations with the Securities and Exchange Commission and Department of Justice alleging multiple accounting and disclosure failures stemming from its classification of EpiPen as a generic drug. This misclassification allowed Mylan to underpay Medicaid rebates by hundreds of millions of dollars and significantly raise the price of EpiPen in the private marketplace. The SEC complaint details how Mylan violated generally accepted accounting principles and other securities laws by failing to disclose the DOJ investigation to investors or accrue for the potential loss contingency, causing earnings to be materially overstated. Mylan also included misleading statements in its disclosures with respect to the government’s position during the investigation. The case demonstrates the importance of professional judgement and the appropriate application of generally accepted accounting principles for public companies. Misclassifying EpiPen allowed Mylan to profit at the expense of the Medicaid, by allowing Mylan to significantly increase the drug price in the private market while avoiding paying the corresponding rebate obligations to Medicaid. The case illustrates how corporate greed can drive fraud, how fraud is strategically committed, and how it is eventually exposed and prosecuted.